ПИТАННЯ СОЦІАЛЬНОЇ ПОЛІТИКИ В КОНЦЕПЦІЇ ПАРТНЕРСТВА ДЕРЖАВИ І БІЗНЕСУ - Golovinov, O.M. (Економіка та право, 2010)
The paper reviews the schools presented by a general economic theory which concern investigation of interactions between economic and social processes personificated by the state and business, in particular public-private partnership. Measures are offered to improve partner relations and their effective impact on the social development of the country.